Islamic Leading School Innovation (Study of Strategies to Improve the Quality of Islamic Schools in North Sumatra) - Dahlinar Dahlinar; Wahyudin Nur Nasution; Afrahul Fadhila Daulay (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Educational innovation has the meaning of creating various new variations, or what can also be calledrenewal, in the implementation of specific learning activities. Innovation also provides a reflection of the modernization of an education system, which refers to the school system or a broader system, namely the national education system. The aim of this research is to critically describe the strategies developed by superior Islamic schools in North Sumatra to improve the quality of education in today's highly competitive times. The presence of leading Islamic schools in various regions of North Sumatra is a symptom that provides new hope in efforts to address the gap in educational quality among Islamic schools in North Sumatra. The research was conducted at three Islamic-based schools, namely, CT Foundation Superior High School, Darul Hasan Padangsidimpuan IT High School, and Shafiyyatul Amaliyyah Medan Private High School. The research was carried out using a field research mechanism, with a description of the findings carried out using aspects and components of qualitative research. The results of the research show that the three schools in this study, Darul Hasan Padangsidimpuan Integrated Islamic High School, CT Foundation Deli Serdang Superior High School, and Medan Plus Shafiyyatul Amaliyyah Private High School, have played a role in improving the quality of superior Islamic educational institutions in the North Sumatra region. One of the indicators is the use of various information technology-based applications and media in learning. Likewise with the use of foreign languages.